ВПЛИВ ЄВРОІНТЕГРАЦІЙНИХ ПРОЦЕСІВ НА СТРАТЕГІЧНУ МОДЕЛЬ ІНВЕСТИЦІЙНО- ІННОВАЦІЙНОГО РОЗВИТКУ РЕГІОНУ (International Journal of Innovative Technologies in Economy, 2018)
The block diagram of the mechanism of her investment providing as key element of the organizational and economic concept as which sources for the purpose of implementation of programs of development of administrative units and other target programs. On the basis of the theory and methodology of regional development and cluster formation and also synergy bases, developed conceptual approach to formation and sustainable development of investment and innovation potential of the region at the heart of which is clever (smart) – specialization.